A case of Susac’s syndrome: bilateral retinal vessel occlusion in the presence of autoimmune inflammatory endotheliopathy (Ukrainian Journal of Ophthalmology, 2025)
The paper presents a case with a classic triad (bilateral inferotemporal branch retinal artery occlusion (BRAO), multifocal callosal micro-infarcts, and sensorineural hearing loss) of Susac’s syndrome in a female patient following COVID-19 infection. We report clinical examination data, particularly, eye examination data and neurological status with brain magnetic resonance imaging (MRI) results. Special attention was given to the diagnostic value of optical coherence tomography (OCT) in Susac’s syndrome, which allows detecting characteristic focal atrophic changes in the inner retina with a preserved structure of the photoreceptor layer. Identification of the typical neurological, ocular or otological symptoms should raise suspicion for the syndrome, which is critical for early administration of the systemic steroid therapy.
Keywords: Susac’s syndrome; autoimmune inflammatory endotheliopayhy; retinal artery occlusion